2009
DOI: 10.1007/s11095-009-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Using Polymer Chemistry to Modulate the Delivery of Neurotrophic Factors from Degradable Microspheres: Delivery of BDNF

Abstract: PLGA-PLL-PEG leads to greater loading and longer-term delivery of BDNF than PLGA or a blend of the polymers. We hypothesize that the introduction of an amphiphilic PLGA-based polymer increases the interaction of the BDNF with the polymer and leads to release that more closely correlates with the degradation of the polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…The solution remaining in the dialysis tube was freeze-dried for 3 days to produce activated PEG-CDI. 17 Then using an excess of activated CDI-PEG-CDI with PLGA-PLL side primary amino chain reaction, the process of polymer dissolution and precipitation was repeated three times until the unconjugated PEG was removed, eventually forming PEG-PLL-PLGA. 18 The drug (DNR, Tet, and NIR797 dye) was directly added into the inner aqueous solution to prepare the drug-loaded PEG-PLL-PLGA.…”
mentioning
confidence: 99%
“…The solution remaining in the dialysis tube was freeze-dried for 3 days to produce activated PEG-CDI. 17 Then using an excess of activated CDI-PEG-CDI with PLGA-PLL side primary amino chain reaction, the process of polymer dissolution and precipitation was repeated three times until the unconjugated PEG was removed, eventually forming PEG-PLL-PLGA. 18 The drug (DNR, Tet, and NIR797 dye) was directly added into the inner aqueous solution to prepare the drug-loaded PEG-PLL-PLGA.…”
mentioning
confidence: 99%
“…IGF-I was continuously released from the microspheres, which likely increased the brain levels of IGF-I over a period of time and resulted in therapeutic effects similar to a continuous subcutaneous infusion of IGF-I [415, 416]. Another study reported a sustained release for up to 60 days of a therapeutic protein, BDNF from PLGA-poly( L-lysine)-PEG microspheres [417]. Although in vivo test was not reported, the bioactivity of the released BDNF was confirmed by cell proliferation and neurite outgrowth in pheochromocytoma PC12 cells stably expressing BDNF cognate receptor TrkB [417].…”
Section: Particle-based Carriers For Cns Delivery Of Proteinsmentioning
confidence: 99%
“…Another study reported a sustained release for up to 60 days of a therapeutic protein, BDNF from PLGA-poly( L-lysine)-PEG microspheres [417]. Although in vivo test was not reported, the bioactivity of the released BDNF was confirmed by cell proliferation and neurite outgrowth in pheochromocytoma PC12 cells stably expressing BDNF cognate receptor TrkB [417]. …”
Section: Particle-based Carriers For Cns Delivery Of Proteinsmentioning
confidence: 99%
“…Drug release is typically dependent on the biodegradation of the material, which can last from hours to months and invoke a host glia response [12][13][14][15]. Drug release is typically dependent on the biodegradation of the material, which can last from hours to months and invoke a host glia response [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Drug release is typically dependent on the biodegradation of the material, which can last from hours to months and invoke a host glia response [12][13][14][15]. Certain factors, such as brain-derived neuronal growth factor, provide neuroprotection and may support neuroplasticity [12,18], whereas other factors, such as vascular endothelial growth factor (VEGF), potentially also strongly affect angiogenesis [19 && ]. Certain factors, such as brain-derived neuronal growth factor, provide neuroprotection and may support neuroplasticity [12,18], whereas other factors, such as vascular endothelial growth factor (VEGF), potentially also strongly affect angiogenesis [19 && ].…”
Section: Introductionmentioning
confidence: 99%